A LOOK AT THE HISTORY OF LEGAL ACTIVITY AND CULTURE FORMATION - A. Yakubov (Bright Mind Publishing, 2025)
This article discusses the role of legal education in the formation of legal activity and culture and the means of its implementation.
Keywords: Legal education, Independence means, one's own life, great law, Oliy Majlis.